NETSseq reveals inflammatory and aging mechanisms in distinct cell types, driving cerebellar decline in ataxia telangiectasia - Stirparo, Giuliano G.; Xu, Xiao; Thompson, Toni; Page, Keith; Harvey, Jenna R. M.; Cadwalladr, David; Lawrence, Jason; Burley, Russell J.; Juvvanapudi, Joel; Roberts, Megan; Barker, Daniel F.; Mulligan, Victoria; et al. (Frontiers in Neuroscience, 2025)
Ataxia–telangiectasia (A–T) is a rare, autosomal recessive, multisystem disorder caused by mutations in the Ataxia–Telangiectasia Mutated (ATM) gene and is characterized by a devastating and progressive neurological pathology. The cellular and molecular changes driving the neurological abnormalities associated with A-T are not well understood. Here, we applied our proprietary Nuclear Enriched Transcript Sort sequencing (NETSseq) platform to investigate changes in cell type composition and gene expression in human cerebellar post-mortem tissue from A-T and control donors. We found dysregulation in neurotransmitter signaling in granule neurons, potentially underlying the impaired motor coordination in A-T. Astrocytes and microglia have evidence of accelerated aging, with astrocytes being characterized by neurotoxic signatures, while microglia showed activation of DNA damage response pathways. Compared to single-nuclei technologies, NETSseq provided a more robust detection of genes with low abundance, a higher cell type specific expression pattern, and significantly lower levels of cross-contamination. These findings highlight the importance of NETSseq as a resource for investigating mechanisms and biological processes associated with disease, providing high-sensitivity, cell-specific insights to advance targeted therapies for neurodegenerative diseases.